Mitevska, Mayana ROLE STRESSORS AND ALIENATION FROM WORK DURING COVID-19 SETTING - Mitevska, Mayiana (Advances in Social Sciences Research Journal, 2021)
Summary: This study explores the interrelationships between work alienation and the role stressor dimensions of ambiguity and conflict. Diagnostics of role stressors in the workplace /Radoslavova, M. 2005/ and Assessment of alienation from work /Velichkov, A. 2005/. The data were collected with an online questionnaire, entered with Google Forms and processed with SPSS-21 using: descriptive statistics, and correlation analysis. The results are compared with similar previous studies conducted in Bulgaria and abroad. Respondents were 75 individuals, 72% of them were doctors working in a government hospital in a regional city. The results of the study showed that role ambiguity is a major workplace stressor in coping with the Covid-19 pandemic. Alienation from work is very high, which is also a significant antecedent for developing Burnout Syndrome.